Microbial Degradation of Low-Density Polyethylene Using a Synergistic Consortium from Landfill Soil - Zahid, Aleena; Batool, Rida; Jamil, Nazia (BioScientific Review, 2025)
Background. Low-density polyethylene (LDPE) is a widely used plastic. A 4-5% annual increase in plastic usage has been observed since the 1960s. Once coined as a ‘‘magic material’’ for its resilience, flexibility, and affordability, plastic has now become an environmental threat due to its severe ecological burden, persistent nature, and non-degradability. The non-degradation of plastic is a major concern in this growing plastic world. The current study investigates the bacterial growth dynamics to degrade LDPE using it as the only carbon source. The bacteria’s potential to grow in stressed environments enhances their bioremediation ability. Methods. Four different types of Gram-positive and Gram-negative bacteria were isolated from the landfill soil sample. After initial screening using the Sherman Manual, bacterial strains were grown in an enriched medium and LDPE was added after pretreatment with UV and ethanol. Results. At the start, no degradation was observed; gradually, the plastic started to degrade. Ultimately, almost 35% of degradation was observed after 60 days of incubation. Various parameters were also studied, including the light microscopic analysis, pH measurement, optical density, and FTIR analysis. During the experiment, the pH decreased, which caused an increase in the metabolic activity of bacteria. As a result of this high metabolic activity, an increase in the optical density of bacteria was observed. Holes were observed in the plastic sheet under the microscope after incubation. Peaks of 1150 cm-1 and 1870 cm-1 were observed in LDPE in the FTIR analysis after incubation in the bacterial consortia. Conclusion. This study reveals the desired/positive effect of bacterial consortia on plastic degradation. Hence, this method can be used to reduce environmental pollution.